Haematological changes and oxygen consumption in Oreochromis mossambicus exposed to sublethal concentrations of lead - James, R; Alagurathinam, S; Sampath, K (Indian Journal of Fisheries, 2011)
The effects of difTerent toxicants on haematological parameters have been investigated (Goel and Kalpana 1985, lIaniffa et at. 1986, Sampath et at. 1993) in fish. Studies on the effect of metal toxicity on oxygen-carrying capacity of blood and recovery of blood cells from metal poisoning in fish,’ however. are lacking. The present paper reports on the sublethal levels of lead on chosen blood parameters and predicts the duration of complete recovery in Oreochromis mossambiicus